Science Fair Success - Bombaugh, Ruth. (Springfield, NJ : Enslow Publishers, 1999)
A guide for choosing, designing, and completing an investigative science fair project, with an appendix listing prize winning projects by students.
Includes bibliographical references and index.
Keywords: Science projects -- Handbooks, manuals, etc; Science projects -- Juvenile literature; Science projects